The fifth general conference of the Asian Forum of Parliamentarians (AFPPD Seretariat, 1996)
This booklet summarizes the proceedings of the Fifth General Conference of the Asian Forum of Parliamentarians on Population and Development (AFPPD) which was held in 1996 in Canberra, Australia. The topic of this conference was food security, population, and development. After a brief introduction which describes the purpose of the AFPPD, the text of the Canberra Statement which arose from the conference is reproduced. The Statement contains a preamble which describes current realities governing the possibility of obtaining food security for the world's population; sections on population growth and food production, food production and the environment, and community development; and a commitment to collective action